The Relationship of Parents' Interpersonal Communication with Sibling Rivalry in Early Childhood at the Kabila Health Center - Wiwik Indrawati Purnama Sari; Ridha Hafid; Bergita Dumar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Sibling rivalry is a competition or rivalry between siblings that arises as a result of the reactions shown by those around them, including parents. One of the factors that influence this phenomenon is the ineffective interpersonal communication of parents. This study aims to determine the relationship between parental interpersonal communication and sibling rivalry in early childhood at the Kabila Health Center. The study used a quantitative approach with a correlational design using a cross sectional approach and involved 106 respondents who were selected through a total sampling technique. The research instrument was in the form of an interpersonal communication questionnaire that referred to the Interpersonal Communication Inventory (ICI) and the sibling rivalry questionnaire. The results of the study using the Spearman Rank test showed a p-value = 0.023 (< 0.05), which indicates that there is a significant relationship between parental interpersonal communication and sibling rivalry in early childhood. In conclusion, the higher the ineffective communication in parents, the greater the incidence rate of sibling rivalry. It is recommended for parents to further improve the quality of effective communication to minimize the occurrence of competition between siblings.